Abemaciclib early access - an Italian experience - Calabrò, Concetta; Cannella, Eleonora; Nardulli, Patrizia (Frontiers in Oncology, 2025)
Italian legislation allows pharmaceutical companies to market drugs authorized through the centralized procedure before price negotiation with the Italian Medicines Agency (AIFA), placing them in the C(nn) category, which indicates non-reimbursed and non-negotiated drugs. Since April 4, 2022, the manufacturer of Verzenios® (Abemaciclib) has made the drug available at a nominal price under the C(nn) classification for its adjuvant treatment of high-risk breast cancer. The MonarchE study showed that Verzenios®, combined with endocrine therapy (ET), reduced the risk of recurrence and distant metastasis by 35% in high-risk patients. The treatment was continued for 24 months, and benefits, including invasive disease-free survival (IDFS) and distant relapse-free survival (DRFS), persisted for up to 48 months, confirming long-term efficacy and tolerability. Results indicated fewer breast cancer-related deaths in the Abemaciclib plus ET arm (4.2%) compared to the ET-only arm (4.9%). Additionally, patients in the control group developed metastatic disease at nearly twice the rate of those receiving Abemaciclib. In Italy, approximately 2,000 patients were treated with Verzenios® in the first year under the C(nn) category without affecting the National Health System’s budget, due to the drug’s symbolic cost. This approach resulted in significant savings by avoiding the full cost of adjuvant therapy and preventing metastatic recurrences. Specifically, managing relapses costs €15,000 per patient, saving around €525,000 per 100 patients treated. Additional savings are expected in the third year, as patients will not require metastatic breast cancer treatment, saving around €17,000 per patient.